Patterns of variation in desiccation resistance in a set of recombinant inbred lines in Drosophila melanogaster - Gomez, Federico Hernan (2015)
Desiccation, resulting from extremely dry environmental conditions, is a serious obstacle to the survival of organisms. Water is vital for the maintenance of intracellular structure and prevents the irreversible formation of aggregates, an occurrence leading to loss of cellular function. To characterize genetic variation in desiccation stress resistance (DSR) in Drosophila melanogaster Meigen, an intercontinental set of recombinant inbred lines (RIL) is used. Flies are exposed to a low humidity environment (<10% relative humidity) at a constant temperature of 25°C. Desiccation stress resistance is higher in RIL derived from a backcross to the parental stock sensitive to heat stress (from Denmark) than in RIL derived from the reciprocal backcross to the heat-stress resistant stock (from Australia). Composite interval mapping reveals significant quantitative trail loci (QTL) for DSR in the set of RIL. Both major and minor effects QTL are detected, suggesting a complex genetic architecture. When compared with a previous investigation performed on the same set of RIL, the present study indicates that not all traits of resistance to environmental stressors are affected in the same direction by segregating co-localized QTL.